Codeswitching in Malaysian Business and Its Role in the Management of Conflict - Morais, Elaine (Journal of Modern Languages, 2017)
This research attempts to delineate some of the patterns of codeswitching, observable in business situations in Malaysia and to spell out some of the implications of this phenomenon for the management of conflict. The study considers Codeswitching as triking feature of business communication in Malaysia, which is found at all levels of the business hierarchy, but is particularly evident at the middle and lower levels.